Green synthesis of ZnO nanoparticles using Antidesma orthogyne extract and their antimicrobial and cytotoxic activities - Bakhtiar, M. Taher; Nik Abd Rahman Zaki, Nik Mawaddah; Md Jaffri, Juliana; Darnis, Deny Susanti; Khotib, Junaidi; Faiyazuddin, Md; Haris, Muhammad Salahuddin (Iranian Chemical Society, 2026)
The green synthesis approach using plant extracts is preferable due to its effectiveness in producing nanoparticles (NPs). In this study, Antidesma orthogyne leaf extract was used to synthesize ZnO-NPs. Phytochemical profiling was conducted using liquid chromatography- mass spectrometry quadrupole time-of-flight, and the synthesized ZnO-NPs were characterized using UV-Vis spectroscopy, dynamic light scattering, zeta potential, scanning electron microscopy (SEM), energy dispersive X-ray (EDX), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Antimicrobial activity was evaluated against selected microorganisms using the disc diffusion method, while cytotoxicity was assessed on MCF-7 human epithelial breast adenocarcinoma cells via MTT assay. The results showed that pH 12 was the optimal condition for ZnO-NP synthesis, yielding NPs with an average size of 131.1 nm and an absorption peak at 351 nm. SEM images indicated slight aggregation, while XRD patterns confirmed the hexagonal wurtzite structure of ZnO-NPs. FTIR and EDX analyses confirmed the formation of ZnO-NPs, and TGA demonstrated thermal stability up to 700°C. In terms of antimicrobial and cytotoxic activities, the ZnO-NPs exhibited notable activities in both assays. Hence, these findings suggest that A. orthogyne extract effectively facilitates ZnO-NP synthesis, producing NPs with potential biomedical applications.